Effect of Nilvadipine in Weak Acidic Medium by 1,1-Diphenyl-2-picryl-hydrazyl (DPPH) Assay - Oyanagui, Yoshihiko; Horiai, Haruo; Ohtsuka, Minoru (Arzneimittelforschung, 2001)
A new medium (pH 5.6 reached by addition of 0.1 mol/l acetate buffer, 37 °C, 60 min) was established for detecting anti-free radical compounds in the 1,1-di-phenyl-2-picrylhydrazyl (DPPH) assay. DPPH bleaching activities of typical anti-oxidants appeared generally weaker at pH 8.0 (the measured ethanol solution pH by the classical DPPH assay method) than at pH 5.6.Nilvadipine (CAS 75530-68-6), a lipo-philic calcium antagonist, enhanced the bleaching much more at pH 5.6 than at pH 8.0. Nifedipine (CAS 21829-25-4) and amlodipine (amlodipine besilate, CAS 88150-42-9) showed some effect, but the other five calcium antagonists failed to bleach DPPH at any pH tested (pH 4.4-8.0). Probucol and β-carotene (standard antioxidant) showed nearly the same bleaching activity as nilvadipine. Captop-ril, glutathione and bilirubin were weaker anti-free radical compounds at pH 5.6. No intermediating participation of superoxide radicals and hydroxyl radicals were observed in the DPPH assay, both at pH 8.0 and 5.6. Thus, nilvadipine was shown to be an efficient free-radical scavenger only at around pH 5.6, a weak acidic condition which may occur as a result of inflammation and/or ischemia-re-perfusion.
Keywords: Amlodipine; CAS 21829-25-4; CAS 75530-68-6; CAS 88150-42-9; 1,1-Diphenyl-2-picrylhydrazyl (DPPH) assay, weak acidic medium; Nifedipine; Nilvadipine